Diabetic Pneumopathy–A New Diabetes-Associated Complication: Mechanisms, Consequences and Treatment Considerations - Kopf, Stefan; Kumar, Varun; Kender, Zoltan; Han, Zhe; Fleming, Thomas; Herzig, Stephan; Nawroth, Peter P. (Frontiers in Endocrinology, 2021)
Patients with diabetes are over-represented among the total cases reported with „idiopathic“ pulmonary fibrosis (IPF). This raises the question, whether this is an association only or whether diabetes itself can cause pulmonary fibrosis. Recent studies in mouse models of type 1 and type 2 diabetes demonstrated that diabetes causes pulmonary fibrosis. Both types of diabetes trigger a cascade, starting with increased DNA damage, an impaired DNA repair, and leading to persistent DNA damage signaling. This response, in turn, induces senescence, a senescence-associated-secretory phenotype (SASP), marked by the release of pro-inflammatory cytokines and growth factors, finally resulting in fibrosis. Restoring DNA repair drives fibrosis into remission, thus proving causality. These data can be translated clinically to patients with type 2 diabetes, characterized by long-term diabetes and albuminuria. Hence there are several arguments, to substitute the term „idiopathic“ pulmonary fibrosis (IPF) in patients with diabetes (and exclusion of other causes of lung diseases) by the term „diabetes-induced pulmonary fibrosis“ (DiPF). However future studies are required to establish this term and to study whether patients with diabetes respond to the established therapies similar to non-diabetic patients.